Analisis Jual Beli Manggis Sistem Borongan Sekali Musim Panen Dalam Perspektif Ekonomi Syari’ah Di Desa Wanasari Kecamatan Wanayasa Kabupaten Purwakarta - Ayi Puspita Sari; Ahmad Saepudin; Siti Rohmat (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
The purpose of this study is to determine the mangosteen buying and selling system in bulk with the agreement of the mangosteen harvest season agreement is appropriate based on the Shari'a contract or there is still a element of gharar in buying and selling mangosteen. The research method used is a qualitative method with a descriptive type case study approach. The technique of data collection is done by triangulation, which is collecting data about the mangosteen trading system in bulk through observation, interviews, and documentation to mangosteen sellers and buyers in the place. Then the results of the study will be analyzed by reducing data, presenting data and drawing conclusions. The results of this study indicate that the sale and purchase of mangosteen in bulk using the contract agreement once the harvest season, done before the mangosteen is feasible to be harvested with the surrender agreement mangosteen submitted when the harvest season arrives on condition that the mangosteen bears fruitful, while the transfer of money is done when the initial contract occurs. If the fruit harvest fails, the buyer's money does not return, but waits for the next bushy mangosteen harvest. Buying and selling mangosteen in bulk in an Islamic economic perspective, including buying and selling gharar or buying and selling supernatural because it does not meet the requirements and the harmony of the sale, there is no clarity in the submission of mangosteen. Advice from the author, buying and selling mangosteen is better done when the mangosteen is harvestable, in order to avoid buying and selling gharar.